Brotherhood [videorecording (DVD)] = $b Broderskab - Donato, Nicolo; Donato, Nicolo; Dencik, David, 1974-; Lindhardt, Thure, 1974-; Bro, Nicolas, 1972-; Holst, Morten; Flygare, Claus (Olive Films, 2010)
Former Danish servicemen Lars and Jimmy are thrown together while training in a neo-Nazi group. Moving from hostility through grudging admiration to friendship and finally passion, events take a darker turn when their illicit relationship is uncovered.